Spaudinių mikrokopijų komplektavimo didžiosiose Lietuvos TSR bibliotekose vystymasis - Urbonas, Viktoras (Knygotyra, 1970)
The first microcopies of printings were acquired by the large libraries in Lithuania after the Second World War for the purpose of filling up the gaps in the library holdings and preservation of unique books. Initially they were obtained from the other libraries of the U. S. S. R.In 1946, the Central Library of the Lithuanian S. S. R. Academy of Sciences started producing photoduplicates of unique books and manuscripts. In 1953, this library obtained the microfilm equipment made by a special order at the Lithuanian Film Studio.At the same time acquisition of microfilms was started at the Scientific Library of the Vilnius State University.Other large libraries of Lithuania started developing acquisition of microfilms in the following years: the National Library in 1959, the Scientific Library of the Kaunas Polytechnic Institute in 1962, the Central Scientific and Technical Library, Kaunas Public Library, Kaunas Medical Institute Library and Vilnius Conservatoire Library in 1963, Lithuanian Agricultural Academy Library in 1964, the Republican Library of Medical Science in 1965, the Library of the Institute of Physical Culture and Sports in 1966.In 1965, microfilms were for the first time used in current acquisition of library holdings, in 1967 the first opaque microcards acquired and equipment for production and usage of transparent microcards obtained by the National library of the Lithuanian S.S.R.In 1968, 60% of all large libraries of Lithuania were practically acquiring microcopies of printings and their holdings reached 1,454,399 copies. The article comprises the data for each library.